UFMC and f-OFDM: Contender Waveforms of 5G Wireless Communication System - Ghasan Ali Hussain; Lukman Audah (IAES Indonesia Section, 2020)
Because of the increased demand for high data rates, looking for using new technologies that meet these requirements are considered a necessary. Hence, Fifth Generation (5G) is expected to be impressive in offering these requirements and implement around 2020. Orthogonal Frequency Division Multiplexing (OFDM) is considered a main technology of LTE wireless communication standards. Due to its suffering from high Bit Error Rate (BER) and Peak Average Power Ratio (PAPR), OFDM doesn't consider as charming solution for future wireless communications and several emerging applications of 5G. Moreover, high Out of Band Emission (OOBE) and inability of supporting the flexible numerology are other demerits of OFDM systems. Thus, looking for alternative waveforms which have the ability of solving OFDM disadvantages are necessary to introduce it as contender candidate for 5G wireless communication systems. In this paper, both of Filtered-OFDM (f-OFDM) and Universal Filtered Multi carrier (UFMC) systems have been discussed for 5G wireless communication systems and compared to OFDM system. The results showed that f-OFDM system is better than both OFDM and UFMC systems and could be introducing as competitive candidate for 5G wireless communication systems because of its ability of reducing OOBE and enhancing BER performance.